Efektivitas Penerapan System E-Planning di Badan Perencanaan dan Pembangunan Daerah (Bappeda) Provinsi Sulawesi Utara - Agung Pratama Paputungan; Marthinus Mandagi; Jeane Mantiri; haeranah haeranah (Institut Pemerintahan Dalam Negeri (IPDN), 2023)
The purpose of this study was to determine the effectiveness of E-Planning in the preparation of the North Sulawesi Provincial RKPD in 2023 at the Regional Planning and Development Agency (BAPPEDA) of North Sulawesi Province, The method used is a qualitative research method, The research location is at the Regional Development Planning Agency (BAPPEDA) Office of North Sulawesi Province. The effectiveness of achieving the goals has been effective where the implementation of e-planning has been very helpful in providing convenience to Bappeda and regional apparatus in preparing the RKPD. For effectiveness, timeliness is not yet effective. Judging from the preparation of the RKPD which took 6 months it could not be completed on time in accordance with the provisions of the applicable regulations. For the effectiveness of human resources is already effective. Judging from the e-planning team that has been able to carry out e-planning well, both in the process of inputting, preparing plans and providing guidance to regional apparatus. For the effectiveness of facilities and infrastructure is already effective. Judging from the availability of supporting facilities and infrastructure such as computers, laptops, printers, wifi, ATK and special e-planning rooms.